LY294002 Inhibits Intermediate Conductance Calcium-Activated Potassium (KCa3.1) Current in Human Glioblastoma Cells - Caglioti, Concetta; Palazzetti, Federico; Monarca, Lorenzo; Lobello, Raffaele; Ceccarini, Maria Rachele; Iannitti, Rossana Giulietta; Russo, Roberta; Ragonese, Francesco; Pennetta, Chiara; De Luca, Antonella; Codini, Michela; Fioretti, Bernard (Frontiers in Physiology, 2022)
Glioblastomas (GB) are the most common tumours with high malignancy and invasiveness of the central nervous system. Several alterations in protein kinase and ion channel activity are involved to maintain the malignancy. Among them, phosphatidylinositol 3-kinase (PI3K) and intermediate conductance calcium activated potassium (KCa3.1) currents are involved in several aspects of glioblastoma biology. By using the electrophysiological approach and noise analysis we observed that KCa3.1 channel activity is LY294002 sensitive and Wortmannin resistant in accord to involvement of PI3K class IIβ (PI3KC2β). This modulation was observed also during endogenous activation of KCa3.1 currents with histamine. The principal action of PI3KC2β regulation was the reduction of open probability in intracellular free calcium saturating concentration. An explanation based on “three gates” model of KCa3.1 channel by PI3KC2β was proposed. Based on the roles of KCa3.1 and PI3KC2β in glioblastoma biology, a therapeutic implication was suggested to prevent chemo and radio resistance mechanisms.